Examining the interaction between language attitudes, cultural identity, and self-rated L2 proficiency: the case of Flemish students learning French and English - Bouyzourn, K (2021)
The aim of the study was to explore the interaction between Flemish secondary school students’ language attitudes, their cultural identity, and their self-rated L2 proficiency for English and French. The study also investigated the influence of (a) age, (b) gender, (c) SES, (d) classification as monolingual or multilingual, (e) self-identification as monolingual or multilingual, (f) self-perceived competence level, (g) knowledge of a language outside the curriculum, and (h) language contact or exposure outside of school on Flemish students’ attitudes towards French and English. A mixed-methods approach to data collection and analysis was employed. Quantitative data was collected through an online questionnaire and analysed using tests of difference and association, and qualitative data was collected through semi-structured follow-up interviews and analysed thematically. Overall, the findings revealed that Flemish students’ attitudes are complex and language-specific, with more positive attitudes towards English than French, which students attributed to the difficulty of the language and the less enjoyable French classes. The results also showed an effect of gender, self-identification as monolingual or multilingual, self-perceived competence level, and language contact or exposure outside of school. Although no relationship was found between cultural identity and language attitudes, the findings did indicate that language attitudes towards French and English are positively correlated with self-rated proficiency for English or French respectively. Such findings highlight the need for L2 language educators and material developers in Flanders to focus on improving students’ learning experience with French by balancing the time spent on grammar rules with engaging (speaking) activities.